I.i.5.g Minutes, - Labour Party (Ireland) (1973)
Minutes of the Administrative Council which took place on 29 Jun 1973 principally concerning: expressions of sympathy to the wife of Senator Paddy Wilson; results of Northern Ireland local elections; Monaghan by-election; motion regarding state funding of political parties; readmission to the party of members of Dublin Corporation; address by Manfred Michel, Secretary-General, Socialist Group of the European Parliament; party finances; resignation of Party Vice-Chairperson. Minutes signed by Donal O’Sullivan, Acting Chair. Also includes: report of the General Secretary; and handwritten text of motion concerning state funding of political parties proposed by Niall Green, and seconded by Donal O’Sullivan. (6 pp)